2005
DOI: 10.2460/ajvr.2005.66.113
|View full text |Cite
|
Sign up to set email alerts
|

Development of a genetically modified nontoxigenic Pasteurella multocida toxin as a candidate for use in vaccines against progressive atrophic rhinitis in pigs

Abstract: Modification by use of S1164A and C1165S leads to a complete loss of toxic effects of PMT without impairment of the ability to induce protective immunity in pigs. Analysis of these results suggests that genetically modified PMT may represent a good candidate for use in developing a vaccine against progressive atrophic rhinitis in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…This toxin is the essential virulence factor in the production of the characteristic lesions of PAR [7]. The method for the administration of purified P. multocida DNT (PmDNT) by the intramuscular route was used to evaluate vaccine containing the PmDNT toxoid [10,19]. Additionally, the PmDNT toxoid is considered an important antigen in vaccines against atrophic rhinitis (AR) [9,11].…”
mentioning
confidence: 99%
“…This toxin is the essential virulence factor in the production of the characteristic lesions of PAR [7]. The method for the administration of purified P. multocida DNT (PmDNT) by the intramuscular route was used to evaluate vaccine containing the PmDNT toxoid [10,19]. Additionally, the PmDNT toxoid is considered an important antigen in vaccines against atrophic rhinitis (AR) [9,11].…”
mentioning
confidence: 99%
“…Recent studies have shown that vaccines contained PMT protein or PMT protein fragments are effective against AR [5][6][7][8][9]12]. In this study, an experimental AR vaccine was developed by replacing the extracted PMT components in commercial vaccines with recombinant Nterminal and C-terminal fragment of PMT expressed in E.coli.…”
Section: Discussionmentioning
confidence: 99%
“…PMT has been considered as a good candidate for vaccine development [3]. Authentic PMT or recombinant PMT or analogues thereof have good immunological effects [3][4][5][6][7][8]. It has been reported that high levels of antibodies can be produced by inoculating sows with a mixture of three recombinant PMT fragments with/without Pasteurella multocida and the antibodies could be transmitted to their offspring with good protection against PMT challenge [9].…”
Section: Introductionmentioning
confidence: 99%
“…The procedures used to determine the titers of Spa antibodies in mouse and pig sera were similar to those described previously (22), with minor modifications. Briefly, polystyrene microtiter plates (96-well assay plate; Becton Dickinson, Franklin Lakes, NJ) were coated overnight at 4°C with 50 l per well of the purified His-tagged recombinant proteins rSpaA, rSpaB, rSpaC664, rSpaC427, and rSpaC253 at concentrations of 5 g/ml in bicarbonate coating buffer.…”
Section: Methodsmentioning
confidence: 99%